Impact toughness of the nanofiber embedded glass fiber-reinforced composites under water absorption condition - Bodur, Mehmet Safa; Avci, Ali (SAGE PUBLICATIONS INC, 2025)
This study examines the impact toughness of nanofiber-reinforced glass fibre composites in water and ozone. Electrospinning and vacuum infusion implanted acrylonitrile-butadiene-styrene (ABS) and polycarbonate (PC) nanofibers in glass fiber-reinforced polymers (GFRP). Nanofiber reinforcement greatly increased water resistance and impact toughness over GFRP. The A10 (ABS-reinforced composite with 10-min electrospinning) had the lowest water absorption (4% after 500 h at 25 degrees C) and maximum impact strength). GFRP absorbed 11% water and had a lower impact strength of 36.2 kJ/m2. Water absorption rates were increased at 65 degrees C, although A10's 6.6% absorption was still best. Under ozone exposure, A10 demonstrated the greatest impact strength of 76 kJ/m2 after 72 h at 50 ppm, whereas the PC-reinforced composite (P30) attained 70 kJ/m2.
Keywords: nanofibers; water immersion; ozone conditioning; impact strength; thermal aging; glass fiber; MECHANICAL-PROPERTIES; MOISTURE DIFFUSION; BRIDGE; Materials Science; Metallurgy & Metallurgical Engineering